Gli anziani nella Chiesa evangelica valdese e nella Chiesa avventista del settimo giorno - Rimoldi, Tiziano ca. 20./21. Jh. (De senectute, 2023)
Although the histories of the two denominations differ, both of their statutes regard the office of elder as an ordinary and permanent ministry for the church, within the frame of presbyterian polity. The two denominations likewise consider that it is the duty of the Church to care for the elderly and thus have set up institutions to look after the specific needs of older people.